2018
DOI: 10.3390/f9090552
|View full text |Cite
|
Sign up to set email alerts
|

Subwatershed-Level Lodgepole Pine Attributes Associated with a Mountain Pine Beetle Outbreak

Abstract: Mountain pine beetle (Dendroctonus ponderosae Hopkins; MPB) is an aggressive bark beetle that attacks numerous Pinus spp. and causes extensive mortality in lodgepole pine (Pinus contorta Douglas ex Loudon; LPP) forests in the western United States and Canada. We used pre-outbreak LPP attributes, cumulative MPB attack severity, and areal extent of mortality data to identify subwatershed-scale forest attributes associated with severe MPB-caused tree mortality that occurred across the Northern Rockies, USA from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…2003, Williams et al. 2018, Negrón 2019), with mean diameters of susceptible lodgepole pine trees smaller than 20 cm and no trees exceeding 40 cm diameter (Appendix : Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2003, Williams et al. 2018, Negrón 2019), with mean diameters of susceptible lodgepole pine trees smaller than 20 cm and no trees exceeding 40 cm diameter (Appendix : Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to treatment timing relative to outbreaks, our finding of a stand-scale effect only in treatments that approximated a clearcut suggests a threshold of thinning intensity needed to foster MPB outbreak resistance. Preoutbreak, the heaviest historical treatments in our study were the only stands below suggested thresholds for MPB outbreak resistance (Mata et al 2003, Williams et al 2018, Negr ón 2019, with mean diameters of susceptible lodgepole pine trees smaller than 20 cm and no trees exceeding 40 cm diameter (Appendix S1: Table S3).…”
Section: Historical Stand-thinning Treatments Fostered Little To No R...mentioning
confidence: 94%
“…Numbers represent order of relative importance and are provided to facilitate comparisons across models. Performance metrics for each model are in Table S1 [Colour figure can be viewed at wileyonlinelibrary.com] where epidemic populations preferred vigorous trees, successively removing the largest diameter trees until few suitable hosts remained (Safranyik & Carroll, 2006;Safranyik et al, 1974;Waring & Pitman, 1985;Williams et al, 2018), and at the landscape scale, where epidemic populations preferred older stands and colonized younger, less optimal stands when few unattacked stands remained (Maclauchlan et al, 2015). Finally, our results suggest that the density-dependent dynamics of short-and long-range dispersal modulated expansion into whitebark pine (Logan et al, 1998;Safranyik et al, 1992).…”
Section: Relative Mean Predictionmentioning
confidence: 99%
“…Thus, irruptive beetle species are usually limited to relatively rare, severely stressed trees during lengthy low‐density periods in which their populations remain relatively stable (Bleiker et al, 2014; Safranyik & Carroll, 2006). However, when populations become high, mass attacks by beetles, a positive density‐dependent change in host selection behavior, can overcome the defenses of nearly all trees, which greatly increases the quantity and quality of available hosts (Boone et al, 2011; Waring & Pitman, 1985; Williams et al, 2018). Mass attacks are made possible by aggregation pheromones that allow rapid recruitment of enough beetles to overcome otherwise efficacious tree defenses (Blomquist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%